2022
DOI: 10.1002/celc.202200555
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Charge Storage Mechanism on Ti3C2 MXene through In Situ Raman Spectroelectrochemistry

Abstract: Current climate issues can be partially remedied through the inclusion of renewable energy sources. However, these energy sources suffer from the need for highly efficient energy storage systems. To this end, studies have been conducted on developing energy storage materials that can provide high energy and power densities. Two-dimensional (2D) carbide and nitride MXenes have the potential to provide both if their mechanism of charge storage is understood. Here, we use in situ/operando Raman spectroelectrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 53 publications
(36 reference statements)
4
23
0
Order By: Relevance
“…which showed slightly larger changes of 0.134e¯$\bar{e}$ in the Ti oxidation state when a larger potential window was applied (0.9 V). [ 31 ] These findings are in line with in situ Raman studies conducted for acidic electrolyte solutions (0.1 m HCl) [ 32,33 ] As can be seen in Figure 2b significant voltage‐dependent changes of the Raman spectra, expressed by a continuous red shifting of the 730 cm −1 bands toward a lower wavenumber of 722 cm −1 were detected upon scanning of the potential from 0.4 to −0.6 V (vs Ag/AgCl). These variations in the observed spectra are attributed to the transition of Ti 3 C 2 O 2 to Ti 3 C 2 O(OH).…”
Section: Mxene Electrodes In Acidic Electrolyte Solutionssupporting
confidence: 82%
See 2 more Smart Citations
“…which showed slightly larger changes of 0.134e¯$\bar{e}$ in the Ti oxidation state when a larger potential window was applied (0.9 V). [ 31 ] These findings are in line with in situ Raman studies conducted for acidic electrolyte solutions (0.1 m HCl) [ 32,33 ] As can be seen in Figure 2b significant voltage‐dependent changes of the Raman spectra, expressed by a continuous red shifting of the 730 cm −1 bands toward a lower wavenumber of 722 cm −1 were detected upon scanning of the potential from 0.4 to −0.6 V (vs Ag/AgCl). These variations in the observed spectra are attributed to the transition of Ti 3 C 2 O 2 to Ti 3 C 2 O(OH).…”
Section: Mxene Electrodes In Acidic Electrolyte Solutionssupporting
confidence: 82%
“…Based on this observation one can assume the occurrence of two charging mechanisms – double layer adsorption of protons which takes place at a positive potential range, and the subsequent protons‐induced surface redox reaction at more negative potentials. [ 32 ] The morphological changes of MXene films during proton insertion/extraction were further evaluated by in situ XRD measurements. [ 34 ] It was found that the changes of the interlayer spacing of the Ti 3 C 2 T x films are strongly affected by the applied voltage – upon charging to −0.6 V a lattice shrinking of 0.1 Å was probed, while further polarization to more negative potentials resulted in a significant expansion of the interlayer space by 0.1 Å (see Figure 2c).…”
Section: Mxene Electrodes In Acidic Electrolyte Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, an increase in the intensity of a certain peak is typically indicative of an increase in the electron density, and consequently, the decrease in the peak intensity corresponds to a decrease in the electron density. 22,35 With this idea, the increase in the intensity of the OH peak when probing the surface corresponds to an increase in the density of adsorbed OH (Fig. 6c).…”
Section: Resultsmentioning
confidence: 96%
“…The Ti 3 C 2 MXene was delaminated in a similar manner as previously reported. 22,35 In short, the as-purchased Ti 3 C 2 MXene (NanoChemAZone 99 wt%) was intercalated using DMSO by stirring for 18 hours. The mixture was then centrifuged at 3500 RPM for 30 minutes (decanting the supernatant and replacing it with water between each centrifuge) until all DMSO was removed, then, the precipitate was membrane ltered and dried in a vacuum oven.…”
Section: Delamination Of Ti 3 C 2 Mxenementioning
confidence: 99%